Dimensional shrinkage, stability and strength properties of oil palm lumber in relation to sawing pattern and resin impregnation treatments / Kamarudin Hassan - Hassan, Kamarudin (Institute of Graduate Studies, UiTM, 2015)
This study focused on the dimensional shrinkage, stability and strength properties of oil palm lumber in relation to sawing pattern and resin impregnation treatments. A total of 26 oil palm trees of high yielding tenera variety were obtained from Sungei Kahang Estate, which is located between latitude N 2°12’24” to N 2°12’55” and longitudes E 103°30’59” to E 103°31’05”. The geographical position of oil palm tree in east and west directions was determined and its position was marked onto the trunk before felling. For basic properties, test samples in pith to periphery zone at different tree heights were analysed by using various analytical techniques. All tests were conducted according to standard test procedures. Based on results, basic properties-related parameters that include vascular bundle, moisture content (MC) and basic density of oil palm lumber were highly dependent on the distance in radial plane with tree heights. For dimensional shrinkage, oil palm billets were sawn into lumber scantlings of different nominal sizes using four types of sawing pattern, namely sawing patterns of type A (SP-A), type B (SP-B), type C (SP-C) and type D (SP-D). After drying, the lumber shrinkage in radial, tangential and its cross-sectional area were measured using a mathematical technique of numeral integrations...